Learning from Fukushima Nuclear power in East Asia - van Ness, Peter; Gurtov, Mel (ANU Press, 2017)
Learning from Fukushima began as a project to respond in a helpful way to the March 2011 triple disaster (earthquake, tsunami, and nuclear meltdown) in north-eastern Japan. It evolved into a collaborative and comprehensive investigation of whether nuclear power was a realistic energy option for East Asia, especially for the 10 member-countries of ASEAN, none of which currently has an operational nuclear power plant. We address all the questions that a country must ask in considering the possibility of nuclear power, including cost of construction, staffing, regulation and liability, decommissioning, disposal of nuclear waste, and the impact on climate change. The authors are physicists, engineers, biologists, a public health physician, and international relations specialists. Each author presents the results of their work.